2015
DOI: 10.1016/j.physbeh.2014.12.045
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine prevents the development of depressive-like behavior in a mouse model of cancer related fatigue

Abstract: Cancer patients frequently suffer from fatigue, a complex syndrome associated with tiredness and depressed mood. Cancer-related fatigue (CRF) can be present at the time of diagnosis, escalates during treatment, and can persist for years after treatment. CRF negatively influences quality of life, limits functional independence, and is associated with decreased survival in patients with incurable disease. We have previously shown that increased pro-inflammatory cytokine expression in the brain contributes to dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 44 publications
2
26
0
Order By: Relevance
“…Fluoxetine administration reduced depressive-like behaviors in tumor-bearing mice, but did not have an effect on KMO mRNA or IDO expression (Norden et al, 2015). On the other hand, in a BV-2 microglial cell line, fluoxetine alone or in combination with acetylsalicylic acid inhibited microglial activation and attenuated LPS-induced production of IL-1β, expression of IDO, and the depletion of 5-HT (Yang et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Fluoxetine administration reduced depressive-like behaviors in tumor-bearing mice, but did not have an effect on KMO mRNA or IDO expression (Norden et al, 2015). On the other hand, in a BV-2 microglial cell line, fluoxetine alone or in combination with acetylsalicylic acid inhibited microglial activation and attenuated LPS-induced production of IL-1β, expression of IDO, and the depletion of 5-HT (Yang et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Traditionally, the major depression is usually considered a disorder associated with microglial overactivation, and this was evidenced by numerous studies. For example, cytokine therapy has been reported to generate depressive symptoms in cancer patients [30,31]. Administrating LPS and/or pro-inflammatory mediators induces depressive-like behaviors including impairment of sucrose preference and loss of hope to escape from despairing environments [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…This is critical as we have previously shown that increased inflammation in the brains of tumor-bearing mice is associated with both fatigue-and depressive like behaviors (19). Administration of minocycline, a broad spectrum antibiotic with anti-inflammatory capacity, inhibited microglial activation in tumor-bearing mice which resulted in reduced neuroinflammation and reduced depressive-like behavior in tumor-bearing mice (11).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased neuroinflammation is thought to induce depressive-like behavior via increased activity of IDO and KMO, which may reduce serotonin synthesis and availability in the brain (43, 44). For example, we have previously shown that treatment with the SSRI Fluoxetine ameliorated depressive-like behavior in tumor bearing mice (19). Here we show that ibuprofen decreased IL-1β and IL-6 mRNA expression in the hippocampus of tumor-bearing mice to levels seen in healthy control mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation